Return on investment of the electronic vaccine intelligence network in India. Issue 1 (31st January 2022) - Gurnani, Vandana; Dhalaria, Pritu; Chatterjee, Susmita; Singh, Prem; Agrahari, Kiran; Kashyap, Satabdi; Bhargava, Ruma; Nandi, Partha; Dhawan, Veena; Aggarwal, Mahesh Kumar; Haldar, Pradeep
ABSTRACT: The electronic vaccine intelligence network (eVIN) was introduced by India's Ministry of Health and Family Welfare in 12 states and was implemented by the United Nations Development Programme through the Gavi health system strengthening support during 2014–17 to replace the traditional paper-based cold-chain management system with an electronic vaccine logistics management system. An economic assessment was conducted as part of the overall assessment of eVIN. The objective of the economic assessment was to conduct a return on investment analysis of eVIN implementation. Return on investment was defined as the ratio of total benefits (savings) from eVIN to total investment in eVIN. All costs were calculated in 2020 prices and reported in Indian rupees (1 US dollar = INR 74.132). A one-rupee investment in eVIN led to a return of INR 0.52 for traditional vaccines. The highest cost savings from eVIN was from better vaccine stock management. When same percentage of savings from the new vaccines were incorporated into the analysis, one-rupee investment in eVIN led to a return of INR 1.41. In the future, when only recurrent costs will exist, the return from eVIN will be even higher: a one-rupee investment in eVIN will yield a return of INR 2.93. The assessment of eVIN showed promising results in streamlining the vaccine flow network and ensuring equity in vaccine stock management along with good return on investment; hence, there was a rapid expansion of eVIN in all 731 districts across 36 states and union territories in the country.